Smoking and the risk of hospitalization for symptomatic diverticular disease: a population-based cohort study from Sweden - Humes, David; Ludvigsson, Jonas F.; Jarvholm, Bengt (Lippincott Williams & Wilkins, 2016)
BACKGROUND: Current studies reporting on the risk of smoking and development of symptomatic diverticular disease have reported conflicting results.